Peningkatan Kapasitas Kader dalam Pengelolaan Sampah Organik dan Anorganik melalui Pelatihan Kompos dan Ecobrick di Dusun Tanjung, Kabupaten Bantul - Huzzi Izza Azzizah; Risma Dwi Astuti; Yosua Henryanto; Zalma Wahyu Rahmawati; Ibnu Rois; Heru Subaris Kasjono (Poltekkes Kemenkes Yogyakarta, 2024)
Waste management, particularly household organic and inorganic waste, has become an increasingly urgent environmental health issue, especially in the Special Region of Yogyakarta following the limited operation of the Piyungan landfill. This condition highlights the need for community-based empowerment in waste management at the source. This community service program aimed to improve community knowledge and skills in managing organic waste through composting and inorganic waste through ecobrick production in Dusun Tanjung, Sewon, Bantul. The program employed a participatory community empowerment approach, consisting of initial engagement, Community Self Survey (CSS), cadre training, and community dissemination. Evaluation was conducted using pre-test and post-test assessments and skill observations. The results showed an increase in participants’ knowledge with a score improvement of more than 20%, and all trained cadres were able to independently practice composting and ecobrick production. The program also demonstrated active participation and successful knowledge transfer by cadres to the broader community. This program contributed to enhancing community capacity in household waste management and has the potential to improve environmental health. Continuous mentoring and strengthening of cadre roles are recommended to ensure program sustainability.